Digestive Tract Morphology, Food and Feeding Habits of the Goby Stigmatogobius pleurostigma (Bleeker, 1849) from the Coastline in Soc Trang - Quang, Dinh Minh; My, Tran Thi Diem (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2, 2018)
This study was conducted along the coastline in Trung Binh Commune, Tran De, Soc Trang from June 2016 to May 2017 to provide useful information on digestive tract morphology, feeding habit and food composition of the goby Stigmatogobius pleurostigma, a commercial fish in the study region. The external morphology of this goby was described additionally to provide information for fish classification. The point analyzing result of preys in the digestive tract of 56 individuals with stomach content out of 215 fish showed that this goby was an omnivorous fish. The food composition of this goby consisted of detritus (82.67%), crustacean (21.67%), fish eggs (6.67%), small fish (1.67%) and zooplankton (3.33%). The food composition of this goby varied with gender and season. The fullness and Clark indices of females: 345.1 ± 55.7 SE and 0.86 ± 0.03 SE; males: 304.3 ± 24.6 SE and 0.84 ± 0.04 SE. The fullness and Clark indices of this goby were 291.9 ± 36.0 SE and 0.92 ± 0.05 SE the wet season, and were 342.2 ± 35.4 SE and 0.78 ± 0.01 SE in the dry season. These results were basis for future aquaculture study of this goby. Keywords Clark index, food composition, fullness index, Stigmatogobius pleurostigma, relative length of the gut References [1] Nguyễn Nhật Thi, Động vật chí Việt Nam - Phân bộ cá Bống Gobioidei, Nxb khoa học và kỹ thuật Hà Nội, Hà Nội, 2000. [2] Mai Đình Yên, Nguyễn Văn Trọng, Nguyễn Văn Thiện, Lê Hoàng Yến & Hứa Bạch Loan, Định loại cá nước ngọt Nam bộ, Nxb Khoa học và Kỹ thuật, Hà Nội, 1992. [3] Nguyễn Văn Hảo, Cá nước ngọt Việt Nam, Nxb Nông nghiệp, Hà Nội, 2005. [4] Trần Đắc Định, Koichi, S., Nguyễn Thanh Phương, Hà Phước Hùng, Trần Xuân Lợi, Mai Văn Hiếu & Kenzo, U., Mô tả định loại cá Đồng bằng sông Cửu Long, Việt Nam, Nxb Đại học Cần Thơ, Cần Thơ, 2013. [5] Diệp Anh Tuấn, Đinh Minh Quang & Trần Đắc Định, Nghiên cứu thành phần loài cá họ Bống trắng (Gobiidae) phân bố ở ven biển tỉnh Sóc Trăng, Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ, 30 (2014) 68-76. [6] Phạm Thị Mỹ Xuân & Trần Đắc Định, Một số đặc điểm sinh sản của cá bống cát Glossogobius giuris (Hamilton, 1822) ở thành phố Cần Thơ, Tạp chí Khoa học Đại học Cần Thơ, 27 (2013) 161-168. [7] Dinh Minh Quang, Morphometrics and condition factor dynamics of the goby Stigmatogobius pleurostigma (Bleeker 1849) during dry and wet seasons in the Mekong Delta, Vietnam, Asian Fisheries Sciences, 30 (2017) 17-25. [8] Cục thống kê tỉnh Sóc Trăng, Niên giám thống kê Sóc Trăng 2015, Nxb Thống kê, Sóc Trăng, 2016. [9] Lê Thông, Nguyễn Minh Tuệ, Nguyễn Văn Phú, Nguyễn Đăng Chúng, Phạm Xuân Hậu, Nguyễn Thị Sơn, Hoàng Văn Chức, Hoàng Phúc Lâm, Lê Huỳnh & Đào Ngọc Cảnh, Các tỉnh thành phố Đồng bằng sông Cửu Long, Nxb Giáo dục, Hà Nội, 2006. [10] Dinh Minh Quang, Nguyen Thi Tra Giang & Nguyen Thi Kieu Tien, Reproductive biology of the mudskipper Boleophthalmus boddarti in Soc Trang, Tap chi Sinh hoc, 37 (2015) 362-369. [11] Nikolsky, G. V., Ecology of fishes, Academic Press, London, United Kingdom, 1963. [12] Nguyễn Vũ Thanh, Nguyễn Ngọc Châu, Nguyễn Đình Tứ, Nguyễn Thanh Hiền, Vanreusel, A. & Smol, N., Động vật đáy hệ sinh thái rừng ngập mặn Cần Giờ, Nxb Khoa học Tự nhiên và Công nghệ, Ha Noi, 2013. [13] Biswas, S. P., Manual of Methods in Fish Biology, South Asian Publishers, 1993. [14] Shorygin, A. A., Feeding and trophic relations of fishes of the Caspian Sea, Pishchepromizdat, Moscow, 1952. [15] Clark, F. N., The weight-length relationship of the California Sardine (Sardina cærulea) at San Pedro, Division of fish and game of California, California, 1928. [16] Wand, M. P., Data-based choice of histogram bin width, The American Statistician, 51 (1997) 59-64. [17] Natarajan, A. V. & Jhingran, A. G., Index of preponderance—a method of grading the food elements in the stomach analysis of fishes Indian Journal of Fisheries, 8 (1961) 54-59. [18] Hyslop, E. J., Stomach contents analysis - a review of methods and their application, Journal of Fish Biology, 17 (1980) 411-429. [19] Dinh Minh Quang, Qin, J. G., Dittmann, S. & Tran Dac Dinh, Seasonal variation of food and feeding in burrowing goby Parapocryptes serperaster (Gobiidae) at different body sizes, Ichthyological Research, 64 (2017) 179-189. [20] Thacker, C. E., Phylogenetic placement of the European sand gobies in Gobionellidae and characterization of gobionellid lineages (Gobiiformes: Gobioidei), Zootaxa, 3619 (2013) 369-382. [21] Thacker, C., Phylogeny of Gobioidei and placement within acanthomorpha, with a new classification and investigation of diversification and character evolution, Copeia, 2009 (2009) 93-104. [22] Võ Thành Toàn & Trần Đắc Định, Nghiên cứu đặc điểm dinh dưỡng cá bống dừa (Oxyeleotris urophthalmus) phân bố dọc theo sông Hậu, Tạp chí Khoa học Đại học Cần Thơ, Thủy sản (2014) 192-197. [23] Trần Hoàng Vũ, Một số đặc điểm sinh học của cá thòi lòi (Priophthalmodon schlosseri) phân bố ở Sóc Trăng và Bạc Liêu, Cao học, Đại học Cần Thơ, 2011. [24] Al-Hussaini, A. H., On the functional morphology of the alimentary tract of some fish in relation to differences in their feeding habits: anatomy and histology, Quarterly Journal of Microscopical Science, 3 (1949) 109-139. [25] Dinh Minh Quang, Preliminary study on dietary composition, feeding activity and fullness index of Boleophthalmus boddarti in Mekong Delta, Vietnam, Tap chi Sinh hoc, 37 (2015) 252-257.